'These Apish Tricks': Newspaper Cartooning and the Struggle for the Labour Party, 1900–19141. Issue 2 (July 2020) - Hyde, Samuel S.
Abstract : The Labour Party's use of cartoons is an underexplored aspect of its history. This article examines the role of cartooning in Labour's formative struggles, as a constituent of the cultural processes that helped shape the Labour alliance, prior to the First World War. From the early campaigns of the Labour Representation Committee (LRC), official cartoon blocks were commissioned for election posters, handbills, and newspapers. Rank and file artists were central to their production, with many seconded from socialist or trade union publications. Prior to the launch of the Daily Citizen in 1912, the organs of local branches and affiliated national bodies were the foremost carriers of pro-Labour cartoons; as the party strove against oppositional rhetoric from Fleet Street. Cartoonists across the alliance promoted the need for unity, but the objectives and tactics around which Labour should unite were contested in their work. Despite the electoral breakthrough of 1906, the Parliamentary Labour Party (PLP) faced dissenting portrayals of their gradualist strategy, propinquity to the Liberals, and reluctance to declare for socialism. With less reverence for the whip and journalistic convention, newspaper cartoonists on the Labour left challenged the course of the party, and the nature of their art.